Ensuring the Balance of Interests in Environmental Resource Use: A Comparative Legal Analysis - Kysylytsia, Nataliia (European Journal of Sustainable Development, 2025)
The interrelation between public and private interests lies at the core of sustainable natural resource management. Although the legal systems of different countries may contain similar formal provisions, the actual balance between these interests is often determined by deeper conceptual, cultural, and political factors. In the field of environmental law and policy, the definition of the concept of “public interest” plays a key role—not only in the distribution of responsibility but also in shaping societal attitudes toward nature. This article explores how public interest in the sphere of environmental resource use is formed and implemented by comparing the approaches of Ukraine and Germany. Despite largely similar private interests and legal regulation, these countries demonstrate fundamentally different environmental outcomes. The article argues that the key difference lies not in the content of legal norms, but in the fundamental political approach and environmental philosophy, particularly in the presence or absence of adaptive governance models. Based on a comparative analysis of four sectors—water use, forest use, subsoil use, and land use—it is shown that Germany applies a more ecocentric, ecosystem-based, and adaptive model of public interest formation. Drawing on this experience, the article examines the possibilities for introducing elements of adaptive environmental policy in Ukraine—in the context of post-war recovery and ecological modernization. Keywords: adaptive governance, public interest, sustainable development, environmental policy, environmental resource use